ANALYSIS OF DAILY CALORIE REQUIREMENTS - Yustinus Tarigan; Jein Jeilen Tampi; Melfa Br Nababan; Hasnur Hasnur; Gylbert Gren Wino; Yusril Saromeng; Andi Nurmutmainnah; Yudha Rello Pambudi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The balance between energy expended and energy consumed plays a crucial role in shaping motor skills, which in turn influences an individual’s ability to perform various physical activities optimally. Understanding daily calorie requirements is therefore essential for supporting physical performance, maintaining health, and preventing nutritional imbalances. This study aims to analyze daily caloric needs through four primary components: Body Mass Index (BMI), Basal Metabolic Rate (BMR), Specific Dynamic Action (SDA), and classifications of energy expenditure based on activity levels. These components provide a comprehensive overview of the metabolic processes that determine individual nutritional demands. A cross-sectional research design was employed to gather data on 38 students enrolled in the Sports Nutrition course within the Physical Education, Health, and Recreation Study Program at Manado State University. BMI was used to categorize participants’ body composition, while BMR calculations helped estimate baseline energy requirements at rest. SDA was incorporated to account for the thermic effect of food during digestion, absorption, and nutrient metabolism. Additionally, daily activities were classified into specific energy categories to evaluate variations in energy expenditure throughout the day. The results of this analysis are expected to contribute valuable insights into students’ nutritional needs, helping tailor dietary recommendations to support their academic and physical training demands. Overall, this study emphasizes the importance of accurate caloric assessment in promoting optimal motor performance and sustaining overall well-being among university students engaged in sports-related disciplines.